Czech Protestants and National Identity: Commemorating Jan Hus in 1869 - Pabian Petr (Filosofický ústav AV ČR, 2009)
In this essay, I will first describe what Czech Protestants expected from the 1869 commemoration of Jan Hus; then how these expectations played out in the public celebrations of the anniversary and, finally, how and why their hopes were frustrated. Contrary to the original expectations of Protestant leaders, the commemoration of the Jan Hus anniversary confirmed the marginal and peripheral position of Protestantism within the national community instead of overcoming it. In addition, the intensive involvement of some Protestant leaders in the liberal commemorative events elicited criticism from the more confessional Protestant elites and thus created a rift within the Protestant community.
Český protestantismus a národní identita: husovské oslavy v roce 1869
Keywords: Jan Hus anniversary, national identities, Czech Protestants; Jan Hus, národní identity, český protestantismus